I fell in love with hope ebook A novel. - Lancali (2023)
Against the unforgiving landscape of a hospital, I fell in love with a mischievous, sun-eyed boy who became my only joy in that desolate place. That's what made it all the more soul-crushing when he committed suicide in front of me. Since then, I've sworn never to love anyone again. With three exceptions: My friends, Sony, Neo, and Coeur, a little gang of rebellious, dying kids. Sony leads the charge with the air of freedom and only one lung to breathe it. Neo, a bad-tempered and wheel-chaired writer, keeps track of our great deeds from stealing to terrorizing our nurse. Coeur is the beautiful boy, the muscle, the gentle giant with a failing heart. Before death inevitably knocks down our doors, my thieves and I have one last heist planned. A great escape that will take us far from abusive parents, crippling loss, and the realities of our diseases. So what happens when someone else walks through the door? What happens when a girl joins our party and renders me speechless with her mischievous smile? What happens when she has suns in her eyes, and as terrified as I am to lose again, I start to fall? Trigger warnings found in foreword Written By Lancali